« Traductions de textes hagiographiques et apocryphes latins en grec » - Gounelle, Rémi (Apocrypha, 2005)
Abstract This study begins with an history of the research on Greek translations of Christian Latin texts and with a discussion of several methodological issues. Then follows an analysis of four examples from the VIIIth to IXth century: pope Zacharias and the Dialogues of Gregory the Great, the menologion of Methodius Ist, Theodore Krithinos and the Passion of Anastasia, the byzantine Gospel of Nicodemus. These examples show that the Iconoclastic controversy has not played an important role in the development of Greek translations of Latin hagiographical and apocryphal texts, contrary to the hypothesis of Ernst von Dobschütz. Abstract Après une histoire de la recherche sur les traductions grecques de textes latins chrétiens et quelques considérations méthodologiques, quatre exemples datables des VIIIe-IXe siècles sont analysés: le pape Zacharie et les Dialogues de Grégoire le Grand, le ménologe de Méthode Ier, Théodore Krithinos et la Passion d'Anastasie, l’Évangile de Nicodème byzantin. L'analyse de ces exemples montre que, contrairement à ce qu'avail suggéré Ernst von Dobschütz, les crises iconoclastes n'ont joué qu'un rôle très indirect dans la traduction de textes hagiographiques et apocryphes du latin en grec.